Boehmite Nanoparticle-enhanced Jatropha Oil Nanofluid: Synthesis, Stability, and Viscosity Analysis - Joshi, Surya Kumari; Chaudhary, Dinesh Kumar; -Mamun, Md Al; Hoque, Sheikh Manjura; Adhikari, Surya Prasad; Dhakal, Rabindra Prasad; Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2025)
The jatropha nanofluid (JNF) was prepared by blending jatropha oil (JO) with 0.1 wt.-% boehmite nanoparticles (B-NPs) and was subsequently characterized for its chemical composition, nanostructural stability, and flow properties using Fourier-transform infrared (FTIR) spectroscopy, zeta potential, and sedimentation tests, and a type B Ostwald viscometer, respectively. X-ray diffraction (XRD) analysis revealed the polycrystalline nature of boehmite with a crystallite size of 8.19 ± 0.57 nm, while Transmission electron microscopy (TEM) showed its platelet-like morphology. With a zeta potential value of 27.3 mV, the nanofluid was suggested to be moderately stable. The addition of B-NPs led to an increase in the kinematic viscosity of jatropha oil, attributed to the enhanced internal resistance caused by suspended nanoparticles. These nanoparticles alter the microstructure of the fluid and influence the formation of interaction layers and particle clusters. The observed enhancement in viscosity suggests that the B-NPs-modified jatropha oil holds potential as an environmentally friendly biolubricant or hydraulic fluid for mechanical applications.